An Analysis of Barriers for the Adoption of Cloud Computing in Education Sector. (August 2014) - Sahdev, Tajinder Singh; Medudula, Murali Krishna; Sagar, Mahim
Cloud computing is an emerging field in information technology, aimed to have access to the IT services anytime, anywhere by authorized personnel. Having wide range of benefits for the organizations or institutes extending to diverse areas including like cost cutting, multi-tenancy, better management of business, highly automated, scalable to suite the ever-changing needs of the organizations or institutes. In the current scenario every emerging and established enterprise wants to implement cloud computing to fulfil their computing needs. If we look at the penetration of education in all regions, there is a dramatic shift from the traditional IT infrastructure offering towards cloud computing. If we go deeper it is evident that with the increase in the number of institutions offering education, cloud computing has come out as a very cost-effective solution for computing and infrastructure needs. This study is an attempt to identify and analyze the key barriers to the adoption of cloud computing in the education sector. Total interpretive structural modelling (TISM) has been used to further develop a hierarchy amongst the various key barriers to cloud adoption in the education sector. This model is intended to classify various barriers to the adoption of cloud computing and for planning of successful infusion of new technologies in the education sector.